(untitled) (المجلة الدولية للبحوث العلمية, 2025)
Objective: The present work aimed to study the histological and ultrastructural effects of cadmium (Cd) on the kidney of rabbit. Materials and Methods: 2 groups of Egyptian adult rabbits were used for this study (4-5 rabbits for each). One group was used as a control and the other group (experimental) was exposed to cadmium intake in a dose of 100mg Cdcl2/L in drinking water for 24 weeks. The animals were killed by cervical dislocation and kidney specimens were taken, fixed and processed for light and electron microscopic examination. Results: The cadmium had adverse effects on the kidney especially the proximal convoluted tubules and the glomerulus. The distal convoluted tubules showed no effects. The proximal tubules showed loss of the basal infoldings, the mitochondria appeared swollen with damaged transverse cristae and some appeared vacuolated. Abundant amount of lysosomes was seen in the cytoplasm. The nucleus appeared irregular in shape and pyknotic in some cells. The apical border of the cells showed disordered and less extensive microvilli. The juxtaglomerular cells in the wall of the afferent glomerular arterioles were loaded with abundant amount of renin granules. The podocytes in the glomerulus appeared disorganized with pyknotic nuclei and degeneration in their pedicles. Conclusion: Cadmium has adverse effects on the kidney even at low concentration. These effects are exclusive on the proximal part of the nephron and present structural changes. Extreme attention must be taken to prevent the release of cadmium to the environment.